EVALUASI KINERJA PEGAWAI DALAM DISTRIBUSI BERAS MISKIN (RASKIN) DI KECAMATAN TEMBALANG KOTA SEMARANG - Nina Widowati (GEMA PUBLICA : Jurnal Manajemen dan Kebijakan Publik, 2015)
The economic crisis and rising fuel prices cause the people of Indonesia isquite worse. Government seeks to issue a policy to assist people who areunderneath of the poverty line by distributing of rice for poor (Raskin). The goalof raskin is to reduce the burden of the poor people (especially for targetedhouseholds) by fulfilling their food needs in the form of rice. Since 2012, thetargeted households can buy only 15 kg of rice at a cost of Rp 1,600/ kg. In fact,there are still some lacks of discretion, due to the role of the village staffs is stilllacking in distributing raskin to the public. Other aspects are improper ontargeting, on amount, on price, punctuality and on quality. Those cause aproblem that needs to get the attention of the government of the village. Thegovernment of village needs to be more proactive in distributing raskin so thatthe problems above can be addressed as soon as possible.Keywords: staff performance; distribution; proactive